PIH1D3-knockout rats exhibit full ciliopathy features and dysfunctional pre-assembly and loading of dynein arms in motile cilia - Zhang, Tingting; Cui, Shiquan; Xiong, Xinrui; Liu, Ying; Cao, Qilin; Xia, Xu-Gang; Zhou, Hongxia (Frontiers in Cell and Developmental Biology, 2023)
Background: Recessive mutation of the X-linked gene PIH1D3 causes familial ciliopathy. PIH1D3 deficiency is associated with the defects of dynein arms in cilia, but how PIH1D3 specifically affects the structure and function of dynein arms is not yet understood. To gain insights into the disease's underlying mechanisms, it is crucial to create a reliable animal model. In the humans, rats, and mice, there is one copy of the PIH1D3 gene on X chromosome. Interestingly, mice have an additional, intronless copy of the Pih1d3 gene on chromosome 1. To develop an accurate disease model, it is best to manipulate the X-linked PIH1D3 gene, which contains essential regulatory sequences within the introns for precise gene expression. This study aimed to develop a tailored rat model for PIH1D3-associated ciliopathy, with the ultimate goal of uncovering the intricate molecular mechanisms responsible for ciliary defects in the disease.Method: Novel Pih1d3 knockout (KO) rats were created by TALEN-mediated non-homologous DNA recombination within fertilized rat eggs and subsequently underwent a comprehensive characterization through a battery of behavioral and pathological assays. A series of biochemical and histological analyses were conducted to elucidate the identity of protein partners that interacts with PIH1D3, thus shedding light on the intricate molecular mechanisms involved in this context.PIH1D3 KO rats reproduced the cardinal features of ciliopathy including situs inversus, defects in spermatocyte survival and in mucociliary clearance, and perinatal hydrocephalus. We revealed the novel function of PIH1D3 in cerebrospinal fluid circulation and elucidated the mechanism by which PIH1D3 deficiency caused communicating hydrocephalus. PIH1D3 interacted with the proteins required for the pre-assembly and uploading of outer and inner dynein arms, regulating the integrity of dynein arm structure and function in cilia.PIH1D3 KO rats faithfully reproduced the cardinal features of ciliopathy associated with PIH1D3 deficiency. PIH1D3 interacted with the proteins responsible for the pre-assembly and uploading of dynein arms in cilia, and its deficiency led to dysfunctional cilia and thus to ciliopathy by affecting the pre-assembly and uploading of dynein arms. The resultant rat model is a valuable tool for mechanistic study of PIH1D3-caused diseases.